A Randomized Trial of Objective Spectacle Prescriptions for Adults with Down Syndrome: Baseline Data and Methods. Issue 1 (January 2021) - Anderson, Heather A.; Benoit, Julia S.; Marsack, Jason D.; Manny, Ruth E.; Ravikumar, Ayeswarya; Fern, Karen D.; Trast, Kelsey R.
Abstract : SIGNIFICANCE: It is difficult to determine the most efficacious refractive correction for individuals with Down syndrome using routine clinical techniques. New objective methods that optimize spectacle corrections for this population may reduce limitations on daily living by improving visual quality. PURPOSE: This article describes the methods and baseline characteristics of study participants in a National Eye Institute–sponsored clinical trial to evaluate objectively derived spectacle corrections in adults with Down syndrome. Intersession repeatability of the primary outcome measure (distance visual acuity) is also reported. METHODS: Adults with Down syndrome were enrolled into a nine-visit study to compare clinically derived spectacle corrections and two different objective spectacle corrections derived from wavefront aberration data. Spectacle corrections were randomized and dispensed for 2 months each. Distance visual acuity was measured with a Bailey-Lovie–style chart. Intersession repeatability of acuity was established by performing difference versus mean analysis from binocular acuity measures obtained through habitual corrections at visits 1 and 2. RESULTS: Thirty adults (mean ± standard deviation age, 29 ± 10 years) with a large range of refractive errors were enrolled. Presenting visual acuity at visit 1 was reduced (right eye, 0.47 ± 0.20 logMAR; left eye, 0.42 ± 0.17 logMAR). The mean difference between visits 1 and 2 was 0.02 ± 0.06 logMAR, with a coefficient of repeatability (1.96 × within-subject standard deviation) of 0.12 logMAR. CONCLUSIONS: This study seeks to investigate new strategies to determine optical corrections that may reduce commonly observed visual deficits in individuals with Down syndrome. The good intersession repeatability of acuity found in this study (six letters) indicates that, despite the presence of reduced acuity, adults with Down syndrome performed the outcome measure for this clinical trial reliably.